THE RATIO OF SILICA FERTILIZATION TO NITROGEN ON RICE PLANT PRODUCTIVITY - Budy Frasetya Taufik Qurrohman; Fitriani Adiningsih; Jajang Supriatna (Gunung Djati Conference Series, 2026)
Rice plants are Si accumulators, but in the field farmers rarely apply silica fertilizer, farmers tend to prioritize nitrogen fertilizer. In fact, rice plants need balanced elements of silica and nitrogen in the soil.. The aim of this research is to determine the effect of application the ratio of silica to nitrogen fertilizer and to obtain the best ratio of silica application to nitrogen fertilizer. The method used in this research was a randomized block design with 6 treatments and 5 replications, the treatments give were: A = control; B = Si: N (0,8); C = Si: N (1); D = Si: N (1,2); E = (Si: N 1,4); F = (Si: N 1,6). As indicators for rice plant productivity in this research were productive tiller, weight of 1000 grains, and rice plant yield per clump. The research results showed that the ratio (0, 8) of applying silica fertilizer to nitrogen fertilizer was potential to increase rice plant productivity.